Religious practices in trauma coping - Khairil Razali (Indonesian Journal of Islam and Muslim Societies, 2013)
Disasters happen in Indonesia current days bring the country into a very disaster-prone country in the Ring of Fire cataclysm. Mega event devastating 2004 tsu-nami in Aceh Province and Nias have serious consequences for vulnerable groupsof parents and children. This paper examines the presence of children in anycatastrophic events, especially related to the psychological impact as well asadequate treatments to reduce and eliminate the prolonged psychological trauma.The 2004 tsunami in Aceh and a number of other natural catastrophic disastershave strengthened the effects of traumatic for children in Aceh and elsewhere inIndonesia. A series of earthquakes has built a-sustainable traumatic attitudeswithin children. This qualitative study learned from children from children cen-ters in Aceh towards their coping strategies and roles of religious practices. Inconclusion that it should be a concern to establish social support systems forchildren to lessen the impact in the future.Bencana yang terjadi di Indonesia dewasa ini menjadikan negara yang sangatrawan bencana dalam Ring of Fire bencana alam. Peristiwa mega dahsyat Tsu-nami 2004 di Provinsi Aceh dan Nias telah berdampak serius bagi kelompok rentanyaitu orang tua dan anak-anak. Tulisan ini mengkaji tentang keberadaan anak-anak dalam setiap peristiwa bencana terutama terkait dengan dampak psikologisbagi  mereka  serta  penanganan  yang  memadai  untuk  mengurangi  danmenghilangkan trauma psikis yang berkepanjangan.Bencana  tsunami  2004  dan  sejumlah  peristiwa  bencana  alam  lainnya  telahmemperkuat dampak-dampak traumatis bagi anak-anak di Aceh dan tempat-tempat lain di Indonesia. Serangkaian gempa bumi telah membangun sikaptraumatis yang berkesinambungan dalam diri anak-anak. Hal ini perlu menjadiperhatian dari sistim dukungan social sekitar anak-anak untuk mengurangi dampaktersebut di masa yang akan datang.